Influence of Pre-Slaughter Environmental Temperature on Meat Quality of Crossbred Pigs of Andhra Pradesh: doi: 10.5958/2581-6616.2021.00010.4 - Mallika, E. Naga; Rao, V. Giridhara; Prasanna, M.; Sree, A. Shilpa; Gowtham, P.; Rao , B. Eswara (Journal of Meat Science, 2021)
This study aimed to investigate the effect of high environmental temperature on meat quality traits of crossbred pigs brought for slaughter to the experimental abattoir of the Department of Livestock Products Technology, NTR College of Veterinary Science, Sri Venkateswara Veterinary University, Andhra Pradesh, India. High pre-slaughter environmental temperature significantly (P<0.05) influenced the meat quality of pigs. Pigs exposed to high environmental temperatures had recorded significantly (P<0.05) lower pH values at 24 hr post-mortem with low heme iron content and recorded significantly higher drip losses. Intramuscular fat and crude protein contents were not affected significantly (P<0.05). Serum lactate, glucose, cortisol, and LDH levels differed significantly with increasing environmental temperatures. A significant correlation was noticed with the levels of LDH to serve as a predictor of meat quality.